Evaluación de la quitina en la producción de almidón termoplástico con base de cáscara de plátano - Macías Bazurto, Josselyn Virginia (2023)
The purpose of this research was to assess the effect of the shrimp exoskeleton tin for the production of thermoplastic starch (TPS) or bioplastic in plantain peel mixture. For the production of the TPS, plantain peel was used from two chip makers, and restaurant shrimp exoskeletons. In addition, laboratory analyses were carried out, characterizing the physical and chemical properties of the plantain peel obtained from the chip makers, assessing ash, fiber, humidity and pH. For the production of thermoplastic starches, plasticizers such as water, acetic acid and glycerol were used. Once the TPS was developed, qualitative tests were carried out using the Likert scale to assess sensory plastic properties (Rigidity, elasticity, opacity, and hardness). The highest-quality bioplastics were T5 treatment (25% plantain peel and 75% quitina). The sensory assessment of these bioplastics indicates that this mixture had a 6.6-point hardness, 0.8-point elasticity, 2.6-point rigidity, and 5.0-point opacity. The ANOVA analysis specified a statistically significant difference between the tights of plastic properties, checking that the chitina acts positively in the development of plantain peel-based bioplastic.